2006
DOI: 10.1080/08037050600586593
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of olmesartan and ramipril on inflammatory response after myocardial infarction in rats

Abstract: This study compares the effect of two different strategies to inhibit the renin-angiotensin system in the setting of acute myocardial infarction (MI). Male Wistar rats were treated with placebo, the angiotensin-converting enzyme (ACE) inhibitor ramipril (1 mg/kg/day), or the AT1 receptor antagonist, olmesartan (1 mg/kg/day), both initiated 1 week before induction of MI and continued for 6 weeks after MI. The inflammatory reaction in the heart was investigated 7 days post-MI by determination of macrophage infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
0
16
1
Order By: Relevance
“…Another important issue to be considered, and closely related to the previous topic, is the effect of RAS blockade on inflammatory infiltrate and the healing process after MI (21,32). In our previous study (12), we found that early long-term therapy with Los in rabbits with MI unfavorably modified ventricular remodeling.…”
Section: Discussionmentioning
confidence: 86%
“…Another important issue to be considered, and closely related to the previous topic, is the effect of RAS blockade on inflammatory infiltrate and the healing process after MI (21,32). In our previous study (12), we found that early long-term therapy with Los in rabbits with MI unfavorably modified ventricular remodeling.…”
Section: Discussionmentioning
confidence: 86%
“…Intravenous valsartan limits IS in rats and dogs [16]. Oral olmesartan (another ARB), started 1 week before infarction and continued for 6 weeks was more effective than the ACE-I ramipril in attenuating remodeling and inflammation in the rat [17]. However, this study did not separate the effects of pretreatment on IR injury from the favorable post-infarction therapeutic effects on remodeling.…”
mentioning
confidence: 81%
“…Although the differences in experimental models are very significant, it may be worth exploring the possibility that the ability of olmesartan to revert to control levels in both anatomical parameters and BNP gene expression in EAM is due to the additional known action of olmesartan on cytokines. In rats with acute myocardial infarction, olmesartan administration improved cardiac function and reduced the infarct size better than ramipril, and it, but not ramipril, decreased macrophage infiltration and decreased IL-1␤ mRNA levels (22). In human peripheral blood mononuclear cells, ramipril did not suppress the genetic expression of IL-1␤ or TNF-␣ as did other ACE inhibitors (23).…”
mentioning
confidence: 85%